Reward Allocations in the United States, Japan, and Korea: A Comparison of Individualistic and Collectivistic Cultures - Kim, Ken I.; Park, Hun-Joon; Suzuki, Nori (Academy of Management Journal, 1990)
This study replicated earlier work comparing reward allocation preferences across countries. Results obtained from student groups from the United States, Japan, and South Korea supported the earlier findings. Most noteworthy was a strong universal reward allocation pattern that approximated the equity norm, according to which, rewards are distributed to group members based on their contributions. However, the groups from the United States and Japan, countries that previous research on culture has identified as respectively very individualistic and very masculine, exhibited a stronger preference for equity than the group from South Korea, a country that earlier data have shown to be neither individualistic nor masculine.